Evaluation Of Social Compliance Training Program Using The Kirkpatrick Model In The Medical Device Company (A Case Study At Pt Xyz) - Andrie Mallisa (UNIVED Press, 2026)
In the medical device industry, compliance with social standards has become increasingly critical. To address these challenges, PT XYZ Indonesia has initiated a Social Compliance Training. This study evaluates the effectiveness of Social Compliance Training conducted at PT XYZ Indonesia using the first three levels of the Kirkpatrick Model: Reaction, Learning, and Behavior. The study used a mixed-method approach involving questionnaires (Level 1), pre- and post-training assessments (Level 2), and interviews and behavioral observations (Level 3). For the level 1 (reaction), findings show that participants react positively to the social compliance training with an average rating of more than 4,5 out of 5. To evaluate the effectiveness of a training program at Level 2 (learning), statistical analysis was conducted using a paired sample t-test. Based on the results of the paired sample t-test, the training program was effective in improving knowledge or skills related to the training content. For level 3 (behavior), the researcher conducted an interview and observation with the head of the department or division. All of the department heads and division heads consider that employees who have attended the training have a better understanding of social compliance and implement it compared to people who have not attended the training.